The Journey of Life and the Quest for Wealth: A Literary Analysis of Poe’s Eldorado - Dwi Anjar Fitriyah; Salsabila Zahrah Hariyana; Shelinda Permata Kaiden (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2025)
Many readers appreciate Eldorado for its narrative appeal, yet the deeper philosophical challenges it raises about humanity’s pursuit of fulfillment often remain overlooked. This study offers a literary analysis of Edgar Allan Poe’s Eldorado, focusing on how the poem portrays human ambition, mortality, and the emotional progression associated with the pursuit of idealized goals. Using a literary analysis approach, the research examines Poe’s use of symbolism, imagery, tone, and poetic structure to explore the knight’s lifelong search for the mythical Eldorado as a metaphor for humanity’s quest for fulfillment and success. The analysis finds that the poem’s symbolic contrasts, rhythmic patterns, and tonal transitions collectively illuminate the psychological and philosophical dimensions embedded in the knight’s journey. In addition, the study situates Eldorado within the broader context of Poe’s writing, emphasizing its alignment with recurring themes in his literary canon, particularly the struggle between idealism and the limitations of human existence. The implications of this research highlight the poem’s continued relevance for literary scholarship and its value for educational and interdisciplinary applications, especially in discussions of ambition, identity, and life transitions. Overall, this study demonstrates that Eldorado functions not only as a narrative of quest but also as a contemplative exploration of hope, disillusionment, and the boundaries of human desire.